Gurrent trends in inclusive primary school Tendências atuais na escola inclusiva tendencias actuales en la escuela primaria inclusive - SamoiIova, Iryna; Kozynets, Oleksandr; Havrylenko, Tetiana; Popadych, Olena; Bondarenko, Yuliia (My University, 2020)
Inclusive education is an important part of the general humanitarian attitude to create equal living conditions and self-realization of various members of society. It is important to diversify approaches to inclusive pedagogy. In particular, the need to take into account age differences in the education of children with disabilities, the need to distinguish inclusive tactics depending on the level of education, the requirement to systematize approaches to inclusive pedagogy from its first structural link and to potentially vocational education. In the system of inclusive education, the primary school occupies a prominent place as the first compulsory educational institution. Aim. The purpose of the article is to consider and analyze current trends in inclusive education in primary school. Methods and instruments. The main research methods are the analysis of the regulatory framework (international policy documents), processing of statistical data, study and generalization of recent publications on the topic with an emphasis on the experience of the leading European countries. Results and conclusion. Further attention to the trends of inclusive education is quite relevant. We have to understand the current and future vectors of inclusive education in the world. Nowadays, inclusive education becomes a trend and a prerequisite for ensuring the principle of parity in the humanities, ensuring equal conditions for human development.
Current trends in inclusive primary school Tendências atuais na escola inclusiva tendencias actuales en la escuela primaria inclusive / I. SamoiIova, O. Kozynets, T. Havrylenko, O. Popadych, Y. Bondarenko // Rev. Tempos Espaços Educ. – V. 13, n. 32, e-14961, jan.-dez. 2020. – С. 1-20.
Keywords: Inclusive education, inclusive education trends, primary school, children with disabilities, children with special needs, special educational needs, primary school student.